MSTN, CKM, and DMRT3 Gene Variants in Different Lines of Quarter Horses - Pereira, Guilherme L. [UNESP]; Matteis, Rafael de [UNESP]; Regitano, Luciana C. A.; Chardulo, Luis Artur L. [UNESP]; Curi, Rogerio A. [UNESP] (Elsevier B.V., 2016)
Single nucleotide polymorphisms (SNPs) in the equine myostatin (MSTN) (g.66493737C>T) and creatine kinase muscle (CKM) (g.22999655C>A) genes have been associated with optimum racing distance and muscle development and racing performance in Thoroughbred horses, respectively. Considering that, since its formation, the Quarter Horse breed has received important genetic influence from the English breed, the genes cited become important candidates for athletic performance in the racing line of the American breed. An SNP in the equine doublesex and mab-3-related transcription factor 3 (DMRT3) gene (g.22999655C>A) has been described, which is responsible for the gait phenotype in homozygous individuals. Using a sample of 296 Quarter Horses of the racing line and 68 animals of the cutting line, the objective of this study was to compare the frequencies of the three SNPs cited above between a random subsample of animals of the cutting line (n = 20) and animals with extreme phenotypes for racing performance (n = 20 per extreme phenotype). The MSTN SNP showed practically no variation, with the observation of only one heterozygous animal (CT) in the cutting line, suggesting that this gene has been under great selective pressure within the racing segment. The CKM gene variant studied was found to be polymorphic, but no significant associates were observed between its alleles and the different lines or groups. Two animals carrying the CA heterozygous DMRT3 genotype were identified in the group with poor racing performance and one in the cutting line, indicating that this variant can be a limiting factor for the development of greater speeds. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Equine; Speed index; Gait; SNP; Myostatin